Two-dimensional analytical model for threshold voltage of graded-channel SOI MOSFETs - Goel V.; Sharma S.; Kumar S.; Jit S. (My University, 2025)
This paper presents a two-dimensional (2D) analytical model for threshold voltage of fully depleted graded-channel silicon-on-insulator (SOI) MOSFETs. The two-dimensional Poisson's equation is solved in different channel regions with parabolic approximation by using suitable boundary conditions. The effect of different device parameters on device performance has been studied. Results confirmed that a graded-channel structure gives better immunity against Short-Channel-Effects (SCEs) in comparison to conventional SOI MOSFETs. The accuracy of the model is verified by comparing the analytical model results with the simulation results obtained by commercially available two-dimensional device simulator, ATLAS. © 2014 IEEE.